Regulatory model for tourism villages in forest areas based on sustainable tourism - Dinda Aprilia; Abdul Kadir Jaelani; Mulyanto Mulyanto; Isharyanto Isharyanto; Itok Dwi Kurniawan (Legality : Jurnal Ilmiah Hukum, 2025)
This study aims to analyse the factors hindering the implementation of sustainable tourism-based regulations in forest area tourism villages and identify the challenges faced by the Tourism Office and tourism managers in achieving sustainable tourism. This study adopts an empirical legal methodology, incorporating primary and secondary data. Primary data was acquired by conducting firsthand observations, comprehensive interviews, and dialogues with pertinent parties, including tourism managers and government officials. Secondary data was collected from legal documents, regional regulations, and government reports. The findings indicate three key factors contributing to ineffective management: (1) an inadequate legal framework lacking clear references to sustainable tourism and ecological justice, (2) weak coordination between Disparpora and Perhutani, leading to poor oversight and synergy, and (3) limited public awareness and weak law enforcement. Additionally, challenges such as minimal community participation, labour and budget constraints, insufficient protection of premium tourism products, and the limited contribution of tourism revenue hinder sustainable tourism implementation. Disparpora and Perhutani have initiated stakeholder engagement, outreach programs, and training sessions to address these issues. However, stronger legal frameworks, improved institutional collaboration, and increased public awareness are essential to achieving sustainable tourism in forest area tourism villages.